Analisis Empiris Pengaruh ROA, Arus Kas Operasional, dan Laba Bersih terhadap Kinerja Saham 10 Perusahaan IDX selama Tahun 2021–2023 - Yudha Panji Wijayanto; Suprihati Suprihati; Rukmini Rukmini; Budiyono Budiyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study investigates the empirical effect of Return on Assets (ROA), Operating Cash Flow, and Net Income on Stock Returns of companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research is motivated by the phenomenon of extreme stock price volatility observed in this timeframe. The population comprises all IDX-listed firms, with purposive sampling resulting in 10 companies observed over three years. Multiple linear regression analysis was conducted using SPSS software. The results reveal that ROA has a positive and significant effect on Stock Returns, with a significance value of 0.042. In contrast, Operating Cash Flow and Net Income do not show significant effects within the model. The Adjusted R-Square value of 0.347 indicates that the independent variables explain 34.7% of the variation in Stock Returns, while the remaining proportion is influenced by other factors outside the model. These findings highlight the importance of profitability indicators, particularly ROA, in explaining stock performance during periods of market volatility.